Análisis prospectivo del sector industrial de plásticos en la ciudad de Bogotá D.C. bajo metodo Delphi (2013)
The article presents the results of the research conducted to determine the strategic factors to keep in mind by the plastics cluster in the city of Bogotá, for the construction of future scenarios to the year 2019 and thus guide the business decisions towards better productivity performance. The paper gives an introduction to the prospective process, which identifies its characteristics and advantages, to then choose the Delphi method as the best technique to achieve consensus among a panel of experts and know their ideas in front of the issues raised. This will set up a set of key variables, which by a structural analysis reach a logical consistent and reliable ordering, which serves as an input for a set of relevant events, interrelated to mark a significant trend that conditions the future behavior of the study industrial sector.